Simulation analysis on the evolution driven model of global copper ore trade network - Chen, Qishen; Wang, Kun; Zhang, Yanfei; Guan, Qing; Xing, Jiayun; Long, Tao; Zheng, Guodong; Li, Qiang; Li, Zhenqing; Ren, Xin; Shang, Chenghong; Duan, Yueran (Frontiers in Physics, 2025)
IntroductionIn the context of energy transition, the competition for copper resources among countries has intensified, and the global copper trade has become a vitally important trade chain. The global copper ore trade network is influenced by various factors, including resource distribution, supply, demand, prices, transportation costs, etc.MethodsTo understand the evolution process of copper trade network and to predict the trend of supply chain structure evolution in future, in this paper, we construct a spatial weighted complex network evolution model based on complex network theory and gravity model using the import and export data and distance data of countries from 1990 to 2022.Results and discussionSimulation results show that the possibility of establishing copper ore trade between countries follows the spatial weighted complex network evolution model. It is proportional to the expected trade flow between countries and inversely proportional to the distance. The model will support the simulation analysis of the supply chain network structure evolution and help to carry out in-depth research on the forecast of future trade relations between important countries.